(untitled) (CIPEEX, 2025)
The InClass project aims to modernize and streamline student attendance tracking in classrooms using geolocation technology. The core idea is to ensure that only students who are physically present within the classroom perimeter can register their attendance, thereby preventing any errors or fraud in attendance records. The system works by having the teacher activate the class session on a mobile app. Once the session is activated, students in the classroom must also activate the app on their devices to have their attendance recorded. What sets the InClass system apart is the requirement for students to stay within the designated perimeter for at least 75% of the class duration for their attendance to be validated. If a student leaves before this minimum time, the system will automatically mark them as absent. This feature ensures that students not only mark their presence but also actively participate in most of the class, fostering more serious and committed engagement with the course material. The technology behind InClass allows the app to monitor real-time location within the classroom boundaries. It leverages the GPS and connectivity features of students’ mobile devices, providing high accuracy in tracking who is present and when. Additionally, the notification system alerts students about the remaining time they need to stay in class to secure their attendance, preventing any confusion or early departures that could result in absences. The geolocation method is secure and adheres to privacy standards, as the data is used solely for attendance tracking and is stored securely. InClass offers a modern and efficient solution for educational institutions, especially universities and schools that want a more advanced and tech-savvy approach to managing student attendance.